2022
DOI: 10.3390/antiox11040690
|View full text |Cite
|
Sign up to set email alerts
|

Lycopus maackianus Makino MeOH Extract Exhibits Antioxidant and Anti-Neuroinflammatory Effects in Neuronal Cells and Zebrafish Model

Abstract: Lycopus maackianus Makino belongs to the Labiatae family and is used in traditional medicine to manage postpartum edema and boils. However, few studies on its antioxidant and anti-inflammatory effects have been conducted. Here, the compounds in L. maackianus methanol (MeOH) extract were profiled using ultra-high-performance liquid chromatography–time-of-flight high-resolution mass spectrometry analysis. The antioxidant activity of L. maackianus MeOH extract was shown to increase in a concentration-dependent ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…These have been widely used in skin care for hundreds of years, and we are currently searching for new natural substances with biological activities. These substances can promote skin health and protect the skin from harmful factors [ 28 , 29 ]. Reports showed that flavonoids from D. odorifera have good therapeutic effects on cardiovascular diseases, blood diseases, and other inflammation-related diseases [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These have been widely used in skin care for hundreds of years, and we are currently searching for new natural substances with biological activities. These substances can promote skin health and protect the skin from harmful factors [ 28 , 29 ]. Reports showed that flavonoids from D. odorifera have good therapeutic effects on cardiovascular diseases, blood diseases, and other inflammation-related diseases [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…ERK, JNK, and p38 respond to oxidative stress, and are activated by ROS production. ERK activation controls cell proliferation; JNK and p38 respond to cell stress and contribute to inflammation and apoptosis [ 29 ]. In our results, latifolin downregulated the phosphorylation of p38 and JNK in t -BHP-induced BJ-5ta cells, but did not affect ERK phosphorylation ( Figure 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…The concentration of every sample is 50-200 µg/mL. For the experimental steps of MTT, please refer to our previous study [19].…”
Section: Cell Culture and Mtt Assaymentioning
confidence: 99%
“…For the methods of UHPLC analysis of the GU1:DHG4 extract, please refer to our previous article [19].…”
Section: Uhplc Analysismentioning
confidence: 99%
“…In addition, the activation of the Nrf2/HO-1 pathway can reduce the NF-κB-mediated inflammatory response to prevent neuronal cell death. Therefore, the Nrf2/HO-1 pathway has been a therapeutic target for neuroprotective medicine [23,24].…”
Section: Introductionmentioning
confidence: 99%